(untitled) (International Association of Biologicals and Computational Digest, 2022)
Date palm is an economically important plant in dry lands of the world, here is an approach towards investigating the Arbuscular Mycorrhizal Fungi diversity and their association with the date palm in Kachchh. The importance lies to the understanding of the root colonization and spore identification with relation to the seasonal change. In the present work soil of non-agricultural land has been taken into consideration to understand the relevance.